Ecologia e etnoecologia de Hypancistrus zebra (Siluriformes: Loricariidae) no rio Xingu, Amazônia brasileira - GONÇALVES, Alany Pedrosa (Universidade Federal do Pará, 2014)
H. Zebra is a fish species of the Loricariidae family, Ancistrinae subfamily, endemic of the Xingu River, with distribution from Belo Monte to the confluence of the Xingu and Iriri rivers. Being a species with great market value aquarist ornamental his capture became rampant, making it an endangered species. Despite strong pressure on H. zebra, there are still few studies on the species. Thus, given the scarcity of basic information and the constant threats, knowing the biology and ecology of H. zebra, aggregating the results of scientific research, also the local ecological knowledge of fishermen ornamental trade about this species becomes an essential tool for the conservation of the species. The distribution of H. zebra is restricted to a small stretch of the Xingu River, between Gorgulho da Rita and Itaubinha, and does not occur evenly, it depends on the presence of boulders. A total of 283 individuals of H. zebra were visualized in the rocky outcrops of the study area, of which 232 were captured. The lowest average abundance was Gorgulho da Rita, as opposed to the site Jericoá with the greatest abundance. Between periods, there was a greater abundance in dry river and lowest value for the period of filling. Environmental factors had no significant influence on the abundance of H. zebra. H. zebra is a generalist species, feeding mainly of periphytic algae, debris, plant debris and sponges, while nematodes and millipedes were considered occasional items. Diet composition and abundance of H. zebra showed no significant differences for collection sites, periods of the year and ontogeny. Considering the composition and abundance of the diet, H. zebra can be considered an iliophagousomnivorous, and ability to adapt changes in food availability in the construction of the Hidroeletric Belo Monte. Ornamental trade fishermen demonstrate expert knowledge concerning the distribution and abundance, habitat, feeding, predation and reproduction of the H. zebra, which can be used to optimize work and to facilitate future management measures. The construction of the Hydroeltric Belo Monte Hydroelectric is a threat to the survival of H. zebra and future studies and monitoring of the species are needed, either as mitigation of impacts, either as to captive breeding as an alternative income coastal communities who depend on fishing on the Xingu river ornamental.